KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA MELALUI PROBLEM BASED LEARNING - Febriyani Putri; Muhammad Hasbi (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This research aimed at finding out (1)the improvement of the ability in creative mathematical thinking, (2) the improvement of the ability in reasoning and creative mathematical thinking for high, medium, and low level students. and (3) the interactions between students’ preliminary ability and the learning approach in improving the reasoning and creative mathematical thinking. By involving PBL in learning requires students to think creatively to generate new ideas in learning. The design of the research was quasi experiment. The sample were the student of VIII.9 at SMPN 31 Padang and the students of VIII.1 at SMPN 25Padang.The result of the research showed that (1) the improvement of students’ ability in creative mathematical thinking for those who were taught by using PBL was better than those who were taught by using the conventional learning, (2) the improvement of students’ ability in creative mathematical thinking for the high, medium, and low level students who were taught by using PBL was better than those who were taught by using the conventional learning, and (3) there was interaction between the preliminary ability and the learning approach to students’ creative mathematical thinking ability.